Liquid Modernity in Shakespeare’s Works: A Critical Reading - Shahid Khan, Farkhanda; Iqbal Qazi, Asma (Pakistan Languages and Humanities Review, 2023)
This work while arguing that Shakespeare has the genius to mingle up words, phrases, and concepts in such a manner that they aptly fit globally- in different regions and countries, scrutinizes Shakespeare’s sublimity through a vast critical scholarship. Not of an age but for all times, was critically remarked by Johnson, who was a contemporary of Shakespeare. His works are sentimental, pithy, and sometimes hilarious. He was the master to develop a connection between the narrative and his characters and that is why we notice, Hamlet’s anger, everlasting love for Romeo and Juliet, Ophelia’s agony, and King Lear’s turning from foolishness to a modest and caring father. Theorists of the postcolonial era offer a variety of reasons for Shakespeare’s recurrent presence around the globe- which are multi-folds, starting from worldwide recognized themes, his genius to transcend class, color or ethnicity, and linguistic barriers.